THE INFLUENCE OF WORK SPIRITUALITY AND ETHICAL INTUITION ON ACCOUNTING DECISION MAKING IN AMBIGUOUS CONDITIONS BY YOUNG PROFESSIONALS IN THE VUCA ERA - Rita J. D. Atarwaman; Zahra Zahra (Adisam Publisher, 2025)
The current professional accounting environment is characterized by VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) dynamics , which increase the potential for ethical dilemmas in financial reporting practices. This situation demands that young professionals be able to make ethical accounting decisions amidst pressure and information ambiguity. This study aims to analyze the influence of work spirituality and ethical intuition on accounting decision-making under ambiguous conditions. An explanatory quantitative approach was used with a survey method on 31 district/city inspectorate auditors in Maluku Province . Data were analyzed using Partial Least Square (SmartPLS 4) . The results showed that work spirituality and ethical intuition had a positive and significant effect on accounting decision-making under ambiguous conditions. The R² value of 0.690 indicated that the two variables were able to explain 69% of the variation in accounting decisions under ambiguous conditions.